Student Engagement dalam Blended Learning: Problematika Interaksi dan Partisipasi Peserta Didik di Era Digital - Mashuri Mashuri; Ridwan Daud; Mawardi (Universitas Islam Negeri Ar-Raniry, 2026)
Digital learning transformation has driven the implementation of blended learning as an approach that integrates face-to-face learning and online learning to improve educational flexibility and access. However, increasing access to technology has not been automatically followed by increased student engagement. In practice, various problems are still found, such as low academic interaction, passive participation, and the emergence of the phenomenon of disengagement which has an impact on the quality of learning experience and learning outcomes. This study aims to analyze the forms of student engagement problems in the implementation of blended learning and identify factors that affect student interaction and participation. The method used is Systematic Literature Review (SLR) with the PRISMA approach, through the process of identification, selection, evaluation and synthesis of relevant scientific publications regarding student involvement in the blended learning environment. The results of the study show that the dimension of behavioral engagement tends to be more visible than the relatively weakened emotional and cognitive involvement. The main inhibiting factors include less interactive learning design, low quality of interaction between lecturers and students as well as between students, limited digital literacy, low motivation to learn, and less than optimal learning environment support. Thus, increasing student engagement requires a reconstruction of blended learning designs that emphasize collaborative interactions, meaningful learning experiences, and adaptive and student-centered technology support.